ANALISIS KEMAMPUAN KOGNITIF DAN SIKAP SISWA PADA MATERI SISTEM SARAF DI KELAS XI SMA NEGERI 2 PERCUT SEI TUAN - Maulida Fitri; M. Yusuf Nasution; Andriani Andriani (Universitas Negeri Medan, 2019)
The purpose of this study was to determine the cognitive abilities and attitudes of students in the nervous system material in class XI of SMA Negeri 2 Percut Sei Tuan Learning Year 2017/2018. The type of research used is descriptive correlational. The population in this study were students of class XI of State Senior High School 2 Percut Sei Tuan 2017/2018 Learning Year totaling 166 people. The sample in this study were 2 classes as many as 84 people in class XI Mia 3 and Mia 4 who were taken by Random sampling. Sources of data from this study are 30 multiple choice tests and 30 question attitude questionnaires. The results showed that the cognitive abilities of students about the nervous system were very good 21.42%, both 51.19%, good enough 13.09%, less good 13.09% and very less 1.09%. The results of the cognitive abilities test of students is good with an average value of 69.87, while the cognitive abilities of students based on indicators on the material of the nervous system (1) 68.45%, (2) 67.52%, (3) 74, 52% good category and (4) 64.28% good enough and the results of the attitude questionnaire showed students' ability both on the indicator received 71.31%, valued 75.49%, organized 71.32%, characteristics 68.92% and sufficient both on the indicator responded to 57.93%. The results of the analysis of testing the hypothesis in this study found that the cognitive abilities and attitudes of students in the nervous system material have a positive and moderate categorical relationship with r count> r table (0.562> 0.214) and t count> t table (6.149> 1.663).Keywords: cognitive ability, attitude, nervous system.